Engineering III–V Semiconductor Nanowires for Device Applications. Issue 18 (17th October 2019) - Wong‐Leung, Jennifer; Yang, Inseok; Li, Ziyuan; Karuturi, Siva Krishna; Fu, Lan; Tan, Hark Hoe; Jagadish, Chennupati
Abstract: III–V semiconductor nanowires offer potential new device applications because of the unique properties associated with their 1D geometry and the ability to create quantum wells and other heterostructures with a radial and an axial geometry. Here, an overview of challenges in the bottom‐up approaches for nanowire synthesis using catalyst and catalyst‐free methods and the growth of axial and radial heterostructures is given. The work on nanowire devices such as lasers, light emitting nanowires, and solar cells and an overview of the top‐down approaches for water splitting technologies is reviewed. The authors conclude with an analysis of the research field and the future research directions. Abstract : With regard to III–V nanowires, the epitaxial growth of axial and radial heterostructures using catalyst and catalyst‐free methods, which are then used for optoelectronic devices such as lasers, light‐emitting diodes, and solar cells, is reviewed. In addition, the top‐down approach to fabricate nanowires for applications in photo‐electrochemical water splitting is also addressed.